2020
DOI: 10.1097/wnr.0000000000001561
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and auditory cortex: using adapted functional near-infrared spectroscopy to measure resting-state functional connectivity

Abstract: Objective Tinnitus, phantom sound perception, arises from aberrant brain activity within auditory cortex. In tinnitus animal models, auditory cortex neurons show increased spontaneous firing and neural synchrony. In humans, similar hyperactivation in auditory cortex has been displayed with functional near-infrared spectroscopy (fNIRS). Resting-state functional connectivity (RSFC) or increased connectivity between brain regions has also been shown in tinnitus using fNIRS. However, current fNIRS techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Tinnitus is proposed to occur when the auditory cortex neurons show increased spontaneous firing and neural synchrony 42 . Supporting this theory, Zenke et al observed an increased auditory cortex activation 37 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tinnitus is proposed to occur when the auditory cortex neurons show increased spontaneous firing and neural synchrony 42 . Supporting this theory, Zenke et al observed an increased auditory cortex activation 37 .…”
Section: Discussionmentioning
confidence: 98%
“…Tinnitus is proposed to occur when the auditory cortex neurons show increased spontaneous firing and neural synchrony. 42 Supporting this theory, Zenke et al observed an increased auditory cortex activation. 37 The authors suggest that a limbic-auditory interaction may be to blame for the presence of tinnitus.…”
Section: Auditory Cortex (Figure 4)mentioning
confidence: 92%
“…Currently, the number of sensors used is relatively small, so that a priori decisions must be made as to which regions’ activity will be recorded and evaluated. Initial studies indicate that cortical changes in tinnitus are not limited to auditory regions 55 , but also affect emotion-relevant regions 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Aktuell ist die Anzahl der verwendeten Sensoren relativ klein, so dass a priori entschieden werden muss, die Aktivität welcher Regionen aufgezeichnet und ausgewertet wird. Erste Untersuchungen weisen auch hier daraufhin, dass sich kortikale Veränderungen bei Tinnitus nicht auf auditive Regionen beschränken 55 , sondern auch hier z. B. emotionsrelevante Regionen betreffen 56 .…”
Section: Schlussfolgerungen Und Ausblickunclassified
“…One study showed increasing intensity of perceived tinnitus with increased gamma band activity of the contralateral auditory cortex 43 whilst another study demonstrated increased gamma band activity in the left and right primary and secondary auditory cortex of tinnitus patients 44 . An innovative functional near-infrared spectroscopy (fNIRS) approach demonstrated increased hemodynamic activity in the AC indicating plasticity changes 45 whereas another fNIRS illustrated increased resting state functional activity in the AC of tinnitus patients vs. non tinnitus individuals 46 . A rat model illustrated augmented cortical excitability post- salicylate induced tinnitus 47 , again reiterating the cellular mechanism of hyperactivity 47 discussed previously but now in the context of the AC.…”
Section: Mechanisms Of Tinnitus Generationmentioning
confidence: 99%